Extracorporeal Membrane Oxygenation Blood Flow and Blood Recirculation Compromise Thermodilution-Based Measurements of Cardiac Output - Russ, Martin; Steiner, Elvira; Boemke, Willehad; Busch, Thilo; Melzer-Gartzke, Christoph; Taher, Mahdi; Badulak, Jenelle; Weber-Carstens, Steffen; Swenson, Erik R.; Francis, Roland C. E.; Pickerodt, Philipp A. (Asaio Journal, 2022)
The contribution of veno-venous (VV) extracorporeal membrane oxygenation (ECMO) to systemic oxygen delivery is determined by the ratio of total extracorporeal blood flow (Q˙EC) to cardiac output (Q˙). Thermodilution-based measurements of Q˙ may be compromised by blood recirculating through the ECMO (recirculation fraction; Rf). We measured the effects of Q˙EC and Rf on classic thermodilution-based measurements of Q˙ in six anesthetized pigs. An ultrasound flow probe measured total aortic blood flow (Q˙A0) at the aortic root. Rf was quantified with the ultrasound dilution technique. Q˙EC was set to 0-125% of Q˙A0 and Q˙ was measured using a pulmonary artery catheter (PAC) in healthy and lung injured animals. PAC overestimated Q˙ (Q˙Pa) at all Q˙EC settings compared to Q˙A0. The mean bias between both methods was 2.1 L/min in healthy animals and 2.7 L/min after lung injury. The difference between Q˙Pa and Q˙A0 increased with an Q˙EC of 75-125%/Q˙A0 compared to QEC<50%/Q˙A0. Overestimation of Q˙Pa was highest when Q˙EC resulted in a high Rf. Thus, thermodilution-based measurements can overestimate cardiac output during VV ECMO. The degree of overestimation of Q˙Pa depends on the Q˙EC/Q˙A0 ratio and the recirculation fraction.
CRIS-Team Scopus Importer:2022-11-17
Keywords: acute lung injury; cardiac output measurements; extracorporeal membrane oxygenation; recirculation fraction; thermodilution; veno-venous